If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 1) + 10 = 26 Reorder the terms: 4(1 + 3x) + 10 = 26 (1 * 4 + 3x * 4) + 10 = 26 (4 + 12x) + 10 = 26 Reorder the terms: 4 + 10 + 12x = 26 Combine like terms: 4 + 10 = 14 14 + 12x = 26 Solving 14 + 12x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 12x = 26 + -14 Combine like terms: 14 + -14 = 0 0 + 12x = 26 + -14 12x = 26 + -14 Combine like terms: 26 + -14 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| 6a-10a-3(2a)=50-5(8) | | 4(x+4)=x+37 | | 4(x+5)=5x+23 | | 4xm+5x=10 | | S^2-9x+18=0 | | 2.252*30-29.578*30+5240.216=0 | | 5x+17=9x-8 | | 10x+6(2x+4)=32 | | 360=3x+78+(2x-12) | | 518x=70 | | X=-3x+5 | | 518x=-70 | | 6x^2+5-99=0 | | 5x^2+25x=-20 | | 212x-5000-x^2=0 | | 37(14x)+28(21x)=[72-72]+[-166+96] | | 7(a-2)=2(2a-1) | | -16t^2-4t+930=0 | | 84.487=-.012x^2+1.242x+64.447 | | -14x^2+1400x-29400=0 | | 5a+-11=3a+-3 | | 4x^2-29x+4x=-2x+5 | | 126+(2x+16)= | | 112+(4x-8)= | | (2x+27)+(3x-27)= | | 181-3x=42x+21 | | 6-7x=87-28x | | (5x+3)+63= | | (x+15)+(2x-30)= | | 6u-2=9u+8 | | (3x-44)+(x-24)= | | 4x-70+60= |